Transition from an asylum seeker-specific health service to mainstream primary care for community-based asylum seekers: a qualitative interview study - Genevieve L Fair; Mark F Harris; Mitchell M Smith (Sax Institute, 2018)
Background and aim: Transition of asylum seekers from special-purpose health services to mainstream primary care is both necessary and difficult. This study explores the issues encountered by asylum seekers undergoing this transition in Sydney, Australia. Methods: Qualitative semistructured interviews were conducted with nine asylum seeker patients and nine staff working in the sector. Results: Asylum seekers faced significant challenges in the transition to mainstream primary care. Contributing factors included the complexity of health and immigration systems, the way in which asylum seeker-specific services provide care, lack of understanding and accommodation by mainstream general practioner (GP) services, asylum seekers' own lack of understanding of the health system, mental illness, and social and financial pressures. Conclusions: There is a need for better preparation of asylum seekers for the transition to mainstream primary care. Mainstream GPs and other providers need more education and support so that they can better accommodate the needs of asylum seeker patients. This is an important role for Australia's refugee health services and Primary Health Networks.